(untitled) (World Bulletin of Social Sciences, 2026)
This article provides a comprehensive analysis of the role, technological interconnections, and stylistic features of sculptural art within the multidisciplinary craft system, using the ancient Khorezmian civilization as a case study. The research complexly examines samples of monumental sculpture and terracotta figurines discovered at the Akchakhan-kala (Kazakly-yatkan) site based on archaeological materials. The author scientifically substantiates the integral connection of sculptural knowledge with pottery, construction, and jewelry crafts, specifically focusing on the use of the matrix method and engineering calculations in creating monumental images. Furthermore, the religious-ideological content of sculptures, the visual expression of Zoroastrian symbols, and local cults are revealed through the example of the "Chorasmian Gad" (city patron) figure. The article concludes that the Khorezmian sculptural school represents a synthesis of classical Eastern art traditions and the "animal style" of nomadic peoples